Impact of Early Natural Killer Cell Reconstitution on the Outcomes of T Cell-Replete Allogeneic Hematopoietic Stem Cell Transplantation - Zhou Z; Liu X; Zhang X; Wen S; Hua H; Wang Z; Xu Z; Lu Y; Wang F (Dove Medical Press, 2023)
Ziwei Zhou, Xuan Liu, Xuejun Zhang, Shupeng Wen, Huan Hua, Zhenzhen Wang, Zheng Xu, Yu Lu, Fuxu Wang Department of Hematology, The Second Hospital of Hebei Medical University, Hebei Key Laboratory of Hematology, Shijiazhuang, Hebei 050000, People's Republic of ChinaCorrespondence: Fuxu Wang, Department of Hematology, The Second Hospital of Hebei Medical University, Hebei Key Laboratory of Hematology, No. 215 West Heping Road, Shijiazhuang, Hebei, 050000, People's Republic of China, Tel +86 13931100360, Fax +86 031166003936, Email wfxhebmu@163.comBackground: Early immune reconstitution is crucial to successful outcomes after allogeneic stem cell transplantation (allo-HSCT). However, in T cell-replete HSCT, the impact of natural killer (NK) cells on transplantation outcome and the factors influencing early NK cell reconstitution remain unclear.Methods: In this retrospective study, we analyzed 128 patients with hematological malignancies who received the first T cell-replete allo-HSCT between May 2019 and September 2021. After application of a conditioning regimen, prophylaxis for graft versus host disease (GVHD), and engraftment, the patients received prevention and treatment procedures for cytomegalovirus (CMV) reactivation. NK cells, T lymphocytes and B lymphocytes in peripheral blood were collected and analyzed at 30, 60, 90, 135 and 180 days after transplantation to observe immune cell reconstitution. Overall survival (OS), relapse-free survival (RFS), minimal residual disease (MRD), relapse, and non-relapse mortality (NRM) were evaluated. SPSS 25.0 and R version 4.2.1 were used for statistical analysis.Results: In patients with rapid NK recovery (NK cell count at 30 days post-HSCT [NK30] > 165/μL and 60 days post-HSCT [NK60] > 265/μL), we observed lower rates of NRM, CMV reactivation and acute GVHD (aGVHD). Multivariate analysis indicated that a lower NK30 (≤ 165/μL) was an independent factor associated with inferior OS and RFS. The NK30 and NK60 in patients with CMV reactivation and aGVHD after transplantation were significantly lower than those in patients without these complications. In addition, CD107a expression in NK cells was also significantly lower in patients who experienced aGVHD. Correlation analysis did not find an inhibitory effect of T-lymphocyte subset reconstitution on NK cells in the early stage after transplantation.Conclusion: Rapid NK cell reconstitution early after allo-HSCT had protective effects on NRM and survival. Promoting early NK cell reconstitution represents a new approach to improving the outcomes of allo-HSCT.Keywords: allogeneic hematopoietic stem cell transplantation, immune reconstitution, natural killer cells, T-cell replete, non-relapse mortality